A Case Study of the Factors that Affect Consumer Behavior in IKEA - Sin, Liem Gai; Utama, A.A. Gde Satia; Pandey, Shweta; Pandey, Rudresh; Harsha, Yalla Satya Sai Venkata Sri; Massand, Ajay; Safitri, Adinda Dessy Indriana; Yan, Ng Pui; Kee, Daisy Mui Hung; Yue, Wong Sin; Zhin, Phuan Mun; Hui, Yip Jia (Asia Pacific Journal of Management and Education (APJME), 2021)
Consumer behavior is the study of consumers and the processes they use to choose, apply and dispose of products and services, including consumers’ emotional and behavioral responses. IKEA is a multinational home furnishings company founded in 1943 in Sweden that has grown rapidly. They manage to produce their products and services more widespread not only based on price but create a unique shopping experience. This study aims to examine the factors that affect consumer behavior in IKEA. Various factors like social factors, wide products assortment, price and others are investigated to analyze consumer behavior of IKEA’s customers. Likert Scale was used to get the final results from the questionnaire filled out by the respondents. The questionnaires were distributed to 250 respondents who use IKEA products. The Likert scale will be used to measure a person's perception and attitude or opinion. The results showed that they chose IKEA due to the cost-advantages and wide products assortment as there has uniqueness over IKEA and cannot be compared with other retailers.